Chambers of commerce and Chinese business enterprise in Malaysia - Chin, Yee Whah; Lee, Yok Fee (Dong Jiao Zong Higher Learning Centre, 2012)
The paper deals with the role of the Associated Chinese Chambers of Commerce and Industries of Malaysia (ACCCIM) that represents 17 constituent members located separately in the 13 states of the nation. It will examine how ACCCIM attempts constantly to enhance and create a favourable environment for enterprise development for the Chinese business community. The paper will analyse the intensity of ACCCIM in fostering better domestic business opportunities through joint ventures that involve other ethnic groups in the multiracial and multicultural context of Malaysia and to exert its influence on state economic policies. Its role in assisting the Chinese business community to expand their markets by various means and in weathering the 1997/98 Asian financial crisis and the current global financial crisis will be discussed.